Tourism Infrastructure Development and Transformation of Vegetation Index in Dodola Island of Morotai Island Regency - Yerik Afrianto Singgalen (Universitas Bina Darma, 2022)
The development of tourism infrastructure without control can cause changes in the environmental vegetation index and harm a tourism destination. This study aims to analyze changes in the vegetation index on Dodola Island from 2013-2021 to develop tourism infrastructure. The approach used is remote sensing, namely the Normalized Difference Vegetation Index (NDVI) and Soil Adjusted Vegetation Index (SAVI) using Landsat 8 Operational Land Imager (OLI). NDVI is an index of the greenery or photosynthetic activity of vegetation. Vegetation actively carrying out photosynthesis will absorb most of the red waves of sunlight and reflect higher near-infrared waves. In addition, SAVI is a soil vegetation index adjusted for soil pixels' effect using a vegetation density function. The results of this study indicate a perfect correlation between the NDVI average value and the SAVI average value of 0.996 so that it can be used as data to analyze changes in the vegetation index value on Dodola Island from 2013-2021. The average NDVI value of Dodola Island in 2017 showed a significant decrease to 0.16 from 0.35 in 2016. Likewise, the average SAVI value of Dodola Island in 2017 showed a reduction of 0.12 from 0 .27 in 2016. Although in 2021, the average NDVI value will increase to 0.32 and the average SAVI value to 0.27, stakeholders need to form institutions and establish policies as a preventive measure for the decline in the vegetation index worse than in 2017. Based on the Decree of the State Minister of the Environment No. 201 of 2004 concerning the characteristics of the damage to mangrove forests, the condition of the mangrove area of ​​Dodola Island in 2017 is categorized as damaged and sparse, so that mangrove rehabilitation is necessary. Based on the results of this study, a community-based mangrove ecotourism approach is recommended as an alternative method of sustainable tourism development on Dodola Island.